2019
DOI: 10.1038/s41598-019-51055-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Sihogayonggolmoryeo-tang (Saikokaryukotsuboreito, Chai-Hu-Jia-Long-Gu-Mu-Li-Tang) for post-stroke depression: A systematic review and meta-analysis

Abstract: This systematic review and meta-analysis aimed to analyze the efficacy and safety of Sihogayonggolmoryeo-tang (SGYMT), a classical herbal medicine consisting of 11 herbs, for treatment of post-stroke depression (PSD). Thirteen databases were comprehensively searched from their inception dates until July 2019. Only randomized controlled trials (RCTs) using SGYMT as a monotherapy or adjunctive therapy for PSD patients were included. Where appropriate data were available, meta-analysis was performed and presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Long-term clinical trials or large-scale cohort studies are needed to evaluate the effects of SYM on cardiovascular and cerebrovascular events or mortality in hypertensive patients. Finally, although fatal adverse events induced by SYM were not observed in the included studies or in our previous study [ 42 ], only three studies (42.86%) [ 29 , 33 , 35 ] reported the incidence of adverse events, and therefore, the safety profile of SYM remains unclear. Especially, although there was no age limit in the inclusion criteria for our study, and none of the included studies targeted children or pregnant women.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Long-term clinical trials or large-scale cohort studies are needed to evaluate the effects of SYM on cardiovascular and cerebrovascular events or mortality in hypertensive patients. Finally, although fatal adverse events induced by SYM were not observed in the included studies or in our previous study [ 42 ], only three studies (42.86%) [ 29 , 33 , 35 ] reported the incidence of adverse events, and therefore, the safety profile of SYM remains unclear. Especially, although there was no age limit in the inclusion criteria for our study, and none of the included studies targeted children or pregnant women.…”
Section: Discussionmentioning
confidence: 78%
“…Among them, fire syndrome can be classified as a syndrome related to the liver, heart, stomach, and intestine. Based on the included studies using pattern identification and our previous study [ 42 ], the treatment principles for SYM were aimed at calming the liver and suppressing liver yang hyperactivity. Therefore, it can be assumed that SYM is used by some researchers under the category of fire syndrome, which mainly includes liver qi or liver yang abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed reduction in occipital dominant spike-wave complexes induced by 3-Hz photic stimulation after KRB treatment in Patient 2 suggests that KRB has inhibitory effects on brain irritability. In addition, Saikokaryukotsuboreitou (SRB), a closely related herbal medicine, shares five common crude drugs (cinnamon bark, jujube, oyster shell, longgu, glycyrrhiza, and ginger) with KRB and has been used to treat neurological symptoms ( 24 ), indicating that these drugs exert effects on the brain. Traditionally, both KRB and SRB have been prescribed for parasomnia for hundreds of years.…”
Section: Discussionmentioning
confidence: 99%
“…A previous chart review study suggested that banhahoobaktang showed a significant effect only in patients with PSD with the Yin pattern [51], and cheonwangbosimdan , which is more suitable for the Yang pattern, showed comparable effects to fluoxetine in a non‐inferiority clinical trial [52]. In addition, shihogayonggolmoryeotang was reported to significantly improve the Hamilton Depression Scale than antidepressants in a systematic review (SR) and meta‐analysis (MA) of 21 randomized controlled trials [53].…”
Section: Strokementioning
confidence: 99%